Laparoscopic ovarian transposition prior to pelvic radiation for gynecologic cancer - Brenna E. Swift; Eric Leung; Danielle Vicus; Allan Covens (Elsevier, 2018)
This study evaluates a novel technique of laparoscopic ovarian transposition performed by Gynecologic Oncologists prior to pelvic radiation for gynecologic cancer. A retrospective review was completed of all patients that underwent laparoscopic ovarian transposition from February 2007 to June 2017 at one tertiary care cancer. The technique involves salpingectomy, followed by retroperitoneal dissection to move the ovaries lateral to the hepatic and splenic flexures of the colon. Normal ovarian function was defined by the absence of vasomotor symptoms, FSH and menstrual history (if menstruating). The radiation dose to the ovary was calculated through dose volume histograms from three-dimensional image planning. Ten patients had laparoscopic ovarian transposition, of which, eight patients received post-operative external beam radiation to the pelvis (45-59.4 Gy). Four had additional brachytherapy (35.5-40 Gy). Median age and follow up were 29 years (18-37), and 20 months (6-103). Nine patients had cervical and one had vaginal cancer. Four patients were treated with primary radiation, three had radical trachelectomy with adjuvant radiation, and three had radical hysterectomy with one of three receiving adjuvant radiation. No patients developed vasomotor symptoms (0/8 (95% CI 0-19%)). FSH was normal in 2/2 patients. Menses continued post-radiation in 5/7 women who retained their uterus. The median radiation dose to the right and left ovary was 0.51 (0.23-1.1) Gy and 0.53 (0.23-1.1) Gy, respectively. Laparoscopic ovarian transposition with mobilization to the hepatic and splenic flexures of the colon achieves preservation of ovarian function in women prior to pelvic radiation.